Keterampilan Berbicara Siswa Sebagai Faktor Penunjang Sikap Percaya Diri Siswa Kelas Rendah Sekolah Dasar - Anggun Syahrani; Adrias Adrias; Salmaini Safitri Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Speaking skills are one of the important factors in building students' confidence. Good speaking skills allow students to express ideas, opinions and feelings clearly and effectively. High confidence in speaking can also support students' academic and social success. This study aims to analyze the role of speaking skills as a supporting factor for high school students' self-confidence. The method used is aqualitative method of interview data collection. The results showed that speaking skills are needed in low grade students as well as high grade students. Speaking skills also support students' confidence in their social interactions. This proves that speaking skills are very important in supporting the confidence of elementary school students.